Overheated and Understudied: A Scoping Review of Heat‐Related Health Impacts in the Arabian Peninsula - Anais Teyton; Jennifer Bailey; Eqi Luo; Rahaf Ajaj; Colin Raymond; Cascade Tuholske; Tarik Benmarhnia (GeoHealth, 2025)
Abstract Extreme heat is worsening due to climate change, and, in combination with increasing urban growth, is an escalating public health concern. In the Arabian Peninsula, the wet‐bulb temperature is projected to surpass theoretical human tolerance limits during the 21st century. Yet, heat research in the region has generally not focused on health impacts, and it is unclear how epidemiologic literature has investigated this. We performed a scoping review to examine the existing literature that assessed the relationship between extreme heat and health outcomes in the Arabian Peninsula, collecting papers published from 2010 to 2024 from three databases. We identified and extracted detailed information from a limited number of studies (n = 12). The greatest number of studies were conducted in Kuwait (n = 8), with others in Saudi Arabia (n = 4), and Qatar, Oman, Yemen, and the United Arab Emirates (n = 1 each). Average temperature was the most used exposure (n = 9) assessed at the daily level (n = 10), using one or several meteorological stations (n = 9) from a single city (n = 8). The outcome was predominantly daily‐level (n = 10) mortality (n = 9) assessed at an ecological scale (n = 10) as opposed to the individual scale. While most studies included confounders (n = 10), their selection was not always consistent with best practices. Most papers did not assess effect modification (n = 8), and none investigated modification by land‐cover and land‐use change on the heat‐health relationship. We provide future research recommendations based on our findings. Additional studies are critical to better understand the heat‐health relationship in the Arabian Peninsula, which can aid intervention implementation.